Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity